Potencial das folhas de Rudgea viburnoides (Cham.) Benth (RUBIACEAE) no tratamento da obesidade e suas alterações metabólicas induzidas por dieta em camundongos Balb/c - Juliana Morais Amaral de Almeida (2011)
Obesity is defined as a multifatorial disease characterized by excessive fat accumulation and a chronic low grade inflammation. Some chemicals substances presents in plants are associated with the prevention or treatment of obesity. The Rudgea viburnoides (congonha, congonha-de-bugre or bugre), a common species of Cerrado (Brazilian Savana), is rich in chemicals substances such as polyphenols,flavonoids, triterpenes and saponins. Several studies have shown that these substances have anti-inflammatory and anti-obesity potentials. The present study aim to evaluate whether the crude extract of R. viburnoides was able to modulate the metabolic and inflammatory dysfunction observed in animals fed an isocaloric-high carbohydrate diet. Leaves of the plant were collected, dried, ground and extracted withwater-alcohol solution to 70%. The extracts tested were obtained after complete evaporation of the solvent. The animals were fed isocaloric high-carbohydrate (HC) diet or control diet (C) for 8 weeks. After this period, the HC diet was supplemented during 4 weeks with three different doses 40, 80 and 160 mg / kg of crude extract of R. viburnoides. The animals fed HC diet had higher adiposity, lower glucose tolerance andinsulin sensitivity, higher HOMA-IR and lower HOMA-, higher concentrations of proinflammatory cytokines (TNF-, IL-6) and chemokine (CCL2) in liver and adipose tissue, higher serum concentrations of resistin and lower adiponectin than animals fed C diet. The animals that received the crude extract of R.viburnoides at the lowest dose,although had a similar adiposity in relation to HC animals, showed reversal of glucose intolerance and insulin insensitivity, lower HOMA-IR and higher HOMA-, lower concentrations of proinflammatory cytokines (TNF-, IL-6) and chemokine (CCL2) in liver and adipose tissue, lower serum resistin with no change in adiponectin profile. The treatment with R.viburnoides improved oral glucose tolerance and insulin sensitivity, aswell as systemic and local inflammation of the animals fed diet HC.